2015
DOI: 10.1160/th14-05-0479
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of patients with Glanzmann thrombasthenia and identification of 17 novel mutations

Abstract: Glanzmann thrombasthenia (GT) is an autosomal recessive bleeding disorder characterised by quantitative and/or qualitative defects of the platelet glycoprotein (GP) IIb/IIIa complex, also called integrin αIIbβ3. αIIbβ3 is well known as a platelet fibrinogen receptor and mediates platelet aggregation, firm adhesion, and spreading. This study describes the molecular genetic analyses of 19 patients with GT who were diagnosed on the basis of clinical parameters and platelet analyses. The patients' bleeding signs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…In fact, both substitutions of Arg551 lead to the loss of multiple structuring H‐bonds, with the larger Trp additionally introducing steric encumbrance (Figure a insets). Close to Asp591, Ile596Thr (I565T) has been the object of several reports mostly from Europe, giving rise to type I GT with moderate to severe bleeding (Table ). Two cases have homozygous expression; in the other three, Ile596Thr is part of compound heterozygosity paired with IVS29(+2)T>C, c.3091delC or a well‐characterized Glu355Lys (E324K) missense mutation (French & Coller, ; Jallu et al., ; Ruan et al., ; Sandrock et al., ; Sandrock‐Lang et al., ). Thus Ile596 (localized on Figure a) is a likely mutational hot spot.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, both substitutions of Arg551 lead to the loss of multiple structuring H‐bonds, with the larger Trp additionally introducing steric encumbrance (Figure a insets). Close to Asp591, Ile596Thr (I565T) has been the object of several reports mostly from Europe, giving rise to type I GT with moderate to severe bleeding (Table ). Two cases have homozygous expression; in the other three, Ile596Thr is part of compound heterozygosity paired with IVS29(+2)T>C, c.3091delC or a well‐characterized Glu355Lys (E324K) missense mutation (French & Coller, ; Jallu et al., ; Ruan et al., ; Sandrock et al., ; Sandrock‐Lang et al., ). Thus Ile596 (localized on Figure a) is a likely mutational hot spot.…”
Section: Resultsmentioning
confidence: 99%
“…The novel p.Val206Asp might have similar effects on the structure of the αIIb β‐propeller and blocked ligand binding as shown in the previous studies . Most of the missense mutations in the ITGA2B are located in the β‐propeller region of αIIb . Several studies have shown that they could prevent complex formation as well as prevent processing of pro‐αIIbβ3 within the endoplasmic reticulum and across the Golgi apparatus …”
Section: Discussionmentioning
confidence: 99%
“…Even though patient 4 had only one deletion in ITGA2B in the heterozygous state, the platelet aggregation test and flow cytometric analysis of platelets strongly suggested the diagnosis of GT. There have been some studies describing patients with GT harboring a single heterozygous mutation or no causative mutations in either ITGA2B or ITGB3 . It remains possible that the causative variants could be located in the promoter, conserved intronic regions or in the non‐coding parts of the genes including regulatory elements of ITGA2B and ITGB3 .…”
Section: Discussionmentioning
confidence: 99%
“…突变类 型包括碱基缺失、插入、倒置、转换导致的移码、 无义及错义突变等, 罕见大的基因缺失 [18] . 其中, 错义 突变最为常见, 它们主要影响蛋白加工, 最近也有研 究显示这些突变改变外显子剪切调节序列进而造成 剪切失败 [19] . 另外, 碱基插入或缺失造成的无义突变 也较普遍, 这些突变会伴随剪切异常, 进而造成截断 蛋白及mRNA的不稳定 [20] .…”
Section: Gpⅱb或gpⅲa编码基因itga2b和itgb3的突变是引unclassified